Pengaruh Pencampuran Gum Arab terhadap Karakteristik Sensoris dan Kimia Fruit Leather Mangga Kweni (Mangifera Odorata Griff.) - Getsri Winokan; Teltje Koapaha; Jolanda Lamaega (Jurnal Teknologi Pertanian (Agricultural Technology Journal), 2022)
The purpose of this study was to determine the level of panelists' preference for mango kweni fruit leather with a mixture of gum arabic, analyze the chemical characteristics of mango kweni fruit leather with a mixture of gum arabic and get the treatment with the most preferred arabic gum mixture. The research method used a completely randomized design (CRD) consisting of 5 treatments and 3 replications with Arabic gum mixing. Parameters observed were sensory characteristics (color, aroma, texture and taste) and chemical characteristics (air content, crude fiber content, total sugar content and degree of content). The results showed that the skin of the mango kweni with a mixture of gum arabic was the most preferred by the panelists in terms of color, aroma, texture and taste was treatment E (a mixture of gum arabic 1.5%). In this treatment it has a chemical content of 14.83% water content, 1.80% crude fiber content, 53.42% total sugar content and 3.84 acidity. Keywords: fruit leather; mango kweni; gum arabic